UPAYA PENGUATAN LITERASI KEAGAMAAN SISWA MTS AR-ROIS CENDEKIA SEMARANG MELALUI KAJIAN HADIS - Fatmawati, Ayu; Bisri, Kasan; Islakhiyah, Mazroatul (Institut Agama Islam Negeri (IAIN) Bone, 2023)
There is a lot of data and facts that explain that Indonesia has a low literacy rate. This research aims to examine efforts to strengthen the religious literacy of students at MTs Ar-Rois Cendekia Semarang through the study of hadith which is used as a positive habit because of the importance of strengthening understanding of religion in students' lives. This research is a type of qualitative research with data collection techniques using interviews and observation. The research results show that students' weak religious literacy can be strengthened through positive habits in islamic junior hight school through the study of hadiths which contain various kinds of hadiths, including authentic, hasan and dha'if hadiths. The importance of strengthening religious literacy is to make students more intelligent, critical and selective in sorting information related to religion and can improve social skills, religious character and cross-cultural abilities.